Pasta's History and Role in Healthful Diets. Issue 5 (September 2019) - Webb, Densie
Abstract : Over the years, pasta has gained an unearned reputation as a contributor to health issues, such as weight gain, diabetes, and cardiovascular disease. The sustained popularity of low-carbohydrate diets has further propagated the belief that eating pasta is bad for health, but the evidence is insufficient to support these perceptions. Pasta has a long culinary history as one of the major components of the Mediterranean diet, which has been proven through years of research to be a healthy dietary pattern. Most dry pasta in the United States is enriched with iron, riboflavin, thiamine, and folic acid. A 2-oz serving of dry pasta (about 1 cup, cooked) supplies the equivalent of roughly 100 μg of folic acid, or 25% of the Daily Value, making it an excellent source of the B vitamin, and it is a good source of iron, providing about 10% of the Daily Value. Pasta's unique profile as a low-cost, convenient, versatile, and nutritious food with a long shelf-life establishes an important role for pasta in meeting the nutrient needs of not only the United States, but globally as well.